IDENTIFICATION AND PREVALENCE OF GASTROINTESTINAL PARASITES IN BEEF CATTLE IN SIAK SRI INDRAPURA, RIAU, INDONESIA - Suwanti, Lucia Tri (Indonesian Journal of Tropical and Infectious Disease, 2019)
Gastrointestinal (GI) parasites infection are one of the major constraints cattle farm in tropical countries including Indonesia and some of GI parasites in cattle have the potential to transmit to humans. This study was aimed to identify and determine the level of prevalence of gastrointestinal (GI) parasites in beef cattle in Siak Sri Indrapura District, Riau Province, Indonesia. This research was conducted on 100 beef cattle consisted of, respectively, 32, 34 and 34 cattles from Bungaraya, Sabak Auh, and Dayun sub-district. The characteristic of sample such as age and sex cattle, cage management, feed and drinking water were recorded. Native, sedimentation and sucrose flotation methods were used to find protozoa and eggs worm. We assessed GI parasites based on finding eggs worm, protozoan cyst and coccidial oocysts in stool samples and identification of GI parasite was based on the morphology and size of the eggs worm and cysts or oocysts of protozoan. The result showed that all of 100 feces samples that examined 100% positive infection for parasites. There were eleven types of gastrointestinal parasites that have been identified, 6 genera of protozoan and 5 genera of worms. The prevalence of gastrointestinal parasites in beef cattles in Siak Sri Indrapura District were Blastocystis sp. (100%), Entamoeba sp. (90%), Eimeria sp. (53%), Giardia sp. (7%), Balantidium coli (4%), Cryptosporidium sp. (2%) Oesophagustomum sp. (45%), Toxocara vitulorum (20%), Moniezia expansa (9%), Trichuris sp. (5%), and Fasciola sp. (4%). In conclusion, Siak Sri Indrapura Riau is an endemic GI parasite and this can threaten the health of livestock and potentially as a zoonotic transmission.